Results of Proximal Humeral Fracture Fixation with Anatomical Locking Compression Plate using 6 stepwise Intraoperative Criteria in Surgical Procedures: A Retrospective Study. - Phiphobmongkol, Vajara; Ngamkittidechakul, Sukhum; Bavonratanavech, Suthorn (The Bangkok Medical Journal, 2016)
OBJECTIVE: To report functional and radiological outcomes of open reduction andinternal fixation of proximal humeral fracture with anatomical LCP using 6 stepwiseintraoperative criteria in surgical procedures. MATERIALS AND METHODS: A total of 30 proximal humeral fractures whichwere treated with open reduction and internal fixation with anatomical LCP ofproximal humerus at a Level 1 and a Level 2 trauma center between January 2012 toDecember 2015 were collected. All patients were operated using the sametechnique in the supine position on a radiolucent table. The surgical approach was deltopectoralapproach. The operation was strictly done following 6 stepwise intraoperativeprocedures, this included: Step 1) reduction and fixation of head fragments. Thereference image in the true AP fluoroscopic view named “beetle car” appearance wasapplied in all cases; Step 2) plate positioning with the humeral head, according torecommendation of implant surgical instructions; Step 3) fix the plate to the humeralhead; Step 4) plate positioning to the shaft; Step 5) fix the shaft to the plate includingadditional locking head screws, head and calcar fixation and; Step 6) secure the suturesof the cuff to the plate. All patients received a similar physical therapy program followinginternal fixation. According to the Neer’s classification, there were 13 two-partfractures, 12 three-part fractures and 5 four-part fractures. The functional outcomes,Constant scores, and radiological outcomes (head-shaft angle and complications) wereanalyzed. The mean follow-up time was 18 months.RESULTS: At the end of the follow-up period, all fractures united with acceptablealignment. The mean Constant score for the injured side was 86 points (range 42–92).Head-shaft angle minor varus (115-124) in 5 patients, normal (125-145) 22, minor valgus(146-155) 1 and major valgus (>155) in 2 patients. 2 patients (6.6 %) had complicationswhich was confirmed by radiologic assessment. It was also found that one case hadsecondary intraarticular screw penetration and another had secondary varus duringfollow up. Both of the cases had severe osteoporosis, but no reoperation was required. CONCLUSION: This study reports on the functional and radiological outcomes ofopen reduction and fixation of displaced proximal humeral fracture with anatomicallocking compression plate using these developed 6 stepwise operative procedureswhich showed reasonable good to excellent outcomes with low complications. Thisstudy strongly suggested that the 6 stepwise surgical procedures should be strictlyfollowed in the correct order as a surgical strategy to prevent complications arisingfrom the operative technique of internal fixation of the complex proximal humeralfracture. from the operative technique of internal fixation of the difficult proximal humeralfracture.